2002
DOI: 10.1177/101053950201400208
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Practices Among Malaysian Adults

Abstract: The practice of losing weight is gaining popularity globally with an increase in health consciousness among the general public. A survey was conducted in seven shopping centres in Kuala Lumpur and its neighbouring towns to assess the weight-loss practices of the general public. Out of the 1032 people approached by the researcher, 389 (37.7%) admitted that they had tried to lose weight before. Of these respondents, 50.4% had the wrong perceptions about their weight with 39.1% of the respondents having BMI lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…About 54% and 45% of men and women accurately perceived themselves in self-verbal and visual perception respectively in the present study. This was similar to the findings of previous studies,[ 13 25 ] who reported that 49.6% and 60% of men and women accurately perceived their weight respectively. More than 1/3 rd and about half underestimated themselves in verbal and visual perception respectively in the present study; this may reduce the motivation for an overweight person to lose weight.…”
Section: Discussionsupporting
confidence: 92%
“…About 54% and 45% of men and women accurately perceived themselves in self-verbal and visual perception respectively in the present study. This was similar to the findings of previous studies,[ 13 25 ] who reported that 49.6% and 60% of men and women accurately perceived their weight respectively. More than 1/3 rd and about half underestimated themselves in verbal and visual perception respectively in the present study; this may reduce the motivation for an overweight person to lose weight.…”
Section: Discussionsupporting
confidence: 92%
“…Prevalence was less than that identified by Weiss et al 32 , using National Health and Nutrition Examination Survey (NHANES) data in 2002, than that observed in a Malaysian study carried out by Kong et al 24 and that found by Kruger et al 14 in a study involving the NHIS in 1998.…”
Section: Discussionmentioning
confidence: 69%
“…Nonetheless, few publications evaluate the use of these substances at the population level. Blank et al 23 and a Malaysian study carried out by Konget al 24 , showed that approximately 10% of adults used some herbal product for weight loss. Also, the National Physical Activity and Weight-loss Survey in 2002 25 , found a higher than 15% prevalence rate.…”
Section: % (95%ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is of considerable relevance because accurate information in this area should assist in the evaluation of changes and trends worldwide, in setting priorities for public health initiatives and in planning management of weight control services. (16,19,23,24,32,34,35,38,46,52,53,58,59,86) 4 828 1.21 (16,38,52,58) Use laxatives or diuretics 2, 7 10 13,067 2.92 (15,16,34,35,38,46,52,53,58,86) 5 679 6.19 (15,16,38,52,58) Eat diet foods or products 1, 5 (15,16) *Prevalence indicates the number of respondents out of n study sample that reported using strategies for trying to lose or maintain weight. 1 Study (46) was not accounted for sample size or prevalence rate in this strategy because of assessment differences (several low-calorie foods were assessed separately).…”
Section: Discussionmentioning
confidence: 99%